Establishing reference values for the pubofemoral distance in normal infant medial hips by ultrasound. (April 2021) - Ban, Yongguang; Luan, Qinhua; Shi, Miao; Sun, Bo; Li, Tianyou; Wang, Yanzhou; Lin, Xiangtao; Teng, Jianbo
Background: Measuring the pubofemoral distance (PFD) is important for evaluating the effectiveness of hip reduction in the treatment of developmental dysplasia of the hip (DDH). However, reference PFD values have not been established in normal infants. Purpose: To investigate variations in PFD values measured in normal infant medial hips stratified by age, laterality, and gender. Material and Methods: A total of 240 infants diagnosed with Graf type Ia and/or Graf type Ib hips by ultrasonography were stratified into eight age groups: 0–1 month; 1–2 months; 2–3 months; 3–4 months; 4–5 months; 5–6 months; 6–7 months; and 7–12 months. The bilateral medial hips were scanned with transinguinal ultrasound. The PFD was defined as the distance between the lateral edge of the superior ramus of pubic bone and the medial edge of the femoral head. Inter-observer reproducibility was assessed. Results: Among the 240 infants, there were 371 Graf type Ia hips and 109 Graf type Ib hips. Mean ± SD bilateral PFD values of eight groups were measured separately. There were no significant differences in mean PFD values for left or right hips (t = 0.946, P  = 0.345) or mean bilateral PFD values in male and female infants (t = 1.445, P  = 0.149). Mean PFD values increased linearly with age (left: r = 0.680, P  < 0.0001; right: r = 0.682, P  < 0.0001). Inter-observer reproducibility was excellent. Conclusion: This study established reference PFD values from the medial hip in infants aged 0–12 months. PFD values increased with age, but were not significantly influenced by laterality or gender. These data provide detailed information that can support follow-up of infants treated for DDH.